The Development of Kenik Aljabar Manipulative for Grade VII Students at MTs Tarbiyatul Islamiyah - Wulan Lailatul Wulan; Arini (Global Education Journal, 2026)
Algebraic expressions are often difficult for Grade VII students because the topic requires them to connect symbolic representations with concrete meanings, particularly when identifying coefficients and constants and simplifying algebraic equations. This study aimed to describe the development process and determine the quality of the Kenik Aljabar manipulative as a learning aid for Grade VII students at MTs Tarbiyatul Islamiyah. The study employed research and development using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation. The product was tested with 11 Grade VII students. Data were collected through validation sheets for the product, student response questionnaire, achievement test validation sheet, student response questionnaire, and achievement test. The data were analyzed using quantitative and qualitative descriptive techniques. The findings showed that the product obtained a validity score of 3.39, while the student response questionnaire and achievement test obtained validity scores of 3.50 and 3.35, respectively; all were categorized as valid. The students' response score reached 3.80 in the high category, indicating that the product was practical. The achievement test showed that 9 of 11 students achieved mastery, with an average score of 90.09 and a classical mastery percentage of 81.82%. Therefore, the Kenik Aljabar manipulative with a user guide was valid, practical, and effective for supporting students' understanding of coefficients, constants, and algebraic simplification.